An overview of the major phenomena of the localization of sound sources by normal-hearing, hearing-impaired, and aided listeners - Akeroyd, Michael A. (SAGE, 2014)
Localizing a sound source requires the auditory system to determine its direction and its distance. In general, hearing-impaired listeners do less well in experiments measuring localization performance than normal-hearing listeners, and hearing aids often exacerbate matters. This article summarizes the major experimental effects in direction (and its underlying cues of interaural time differences and interaural level differences) and distance for normal-hearing, hearing-impaired, and aided listeners. Front/back errors and the importance of self-motion are noted. The influence of vision on the localization of real-world sounds is emphasized, such as through the ventriloquist effect or the intriguing link between spatial hearing and visual attention.